The Existence of Traditional Games in Bangka Belitung as a Character Formation for Students - Sugiyarti, Sri; Feri Ardiansah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Traditional games in the context of elementary education help preserve local cultures, which are increasingly threatened by globalization and modernization. By introducing traditional games, students recognize and appreciate the cultural heritage of their communities. Globalization has significantly impacted the development of knowledge, education, economics, and culture. At the elementary school level, globalization also influences student behavior, such as increased interest in foreign cultures and decreased participation in local cultural activities. Therefore, it is crucial for students to recognize their culture through various channels. To this end, this study examined the existence of traditional games in schools, whether they are still recognized, and which games students are familiar with. This study used qualitative methods with an exploratory approach. The results show that traditional games still exist, but their implementation is uneven and not yet fully structured. The majority of students are familiar with traditional games such as cak lingking, gasing, and gobak sodor, bentengan, but their frequency has decreased due to the influence of digital games and changes in play patterns. Physical education teachers teach traditional games, but limited time, equipment, and resources hinder their systematic implementation. Schools with a clear cultural vision incorporate traditional games into their curriculum and thematic activities. In other schools, activities are spontaneous and not yet documented in official programs. While all schools consider traditional games effective in building character, cooperation, sportsmanship, and a love of local culture, most schools have not incorporated traditional games into structured curriculum-based programs.